LOOKING FOR SOURCES OF AN OPHIOLITIC MÉLANGE: THE CASE OF RHODES (DODECANESE, GREECE) AND ITS TIES WITH EASTERN MEDITERRANEAN UNITS - Cordey, Fabrice (Ofioliti, 2022)
The ophiolites and related mélanges in the Eastern Mediterranean region are important proxies for tracking the geodynamic evolution of the Paleotethyan and Neotethyan basins. Along the Aegean forearc, the island of Rhodes (Dodecanese, Greece) is located at a key position between the western and eastern ophiolites of the region and exposes an ophiolitic mélange unit (“Kopria Mélange”) comprising sedimentary and magmatic rocks of Paleozoic and Mesozoic ages, but no clear understanding of their relationships. New micropaleontological results obtained on radiolarian cherts show that some blocks in the mélange are Middle Jurassic (early Aalenian), Late Jurassic (late Kimmeridgian), and Early Cretaceous (Valanginian; late Valanginian-early Aptian) in age, complementing previous data obtained on blocks with sedimentary and magmatic sources (Early or early Late Carboniferous to Late Cretaceous). The mélange components age range (MCAR) of the Kopria Mélange, a new indicator corresponding to the time span represented by all the elements in a given mélange, reaches a significant duration of 239±9 million years. A review of the nature and ages of the Kopria blocks shows that the mélange is probably polygenetic and could record 1) Paleozoic units derived from the southernmost part of the northern Paleotethyan margin; 2) the local Prophitis Ilias Unit traditionally associated with the Pindos Zone s.l. of continental Greece, Peloponnesus and Crete; and 3) potential remnants of the sedimentary cover of the Rhodes ophiolite. It is difficult to determine whether the mélange formed exclusively during obduction or was related to subduction-accretion processes associated with stacking of upper and lower plate components. However, the co-occurrence of ophiolitic blocks with Jurassic and Cretaceous ages reveals a double magmatic signature which could represent the transition between units comprising the Middle-Late Jurassic ophiolites traditionally associated with the Hellenides, and the Cretaceous ophiolites correlated with the Taurides (Lycian Nappes). These results show that the ophiolitic mélange of Rhodes possibly records sources from two distinct and diachronous parts of the Northern Neotethyan basin